Estimation of the drag coefficient from the upper ocean response to a hurricane: a variational data assimilation approach - Zedler, Sarah; Kanschat, Guido (Ocean modelling online, 2013)
We seek to determine whether a small number of measurements of upper ocean temperature and currents can be used to make estimates of the drag coefficient that have a smaller range of uncertainty than previously found. We adopt a numerical approach in an inverse problem setup using an ocean model and its adjoint, to assimilate data and to adjust the drag coefficient parameterization (here the free parameter) with wind speed that corresponds to the minimum of a model minus data misfit or cost function. Pseudo data are generated from a reference forward simulation, and are perturbed with different levels of Gaussian distributed noise. It is found that it is necessary to assimilate both surface current speed and temperature data to obtain improvement over previous estimates of the drag coefficient.